Osseous Metaplasia in Adenocarcinoma - Phiza Aggarwal; RPS Punia; Robin Kaushik; Manveen Kaur; Deepak Aggarwal (Journal of Clinical and Diagnostic Research, 2018)
Osseous Metaplasia (OM) or heterotopic ossification is a rare phenomenon with unknown aetiology that is characterised by the formation of mature bone elements in the stroma of different tumors. Awareness of this condition is important to avoid diagnostic confusion with carcinosarcoma and local bone invasions that have different lines of treatment and prognosis. Here, authors report two cases of heterotopic ossification in adenocarcinoma of sigmoid colon and lung and provide salient features that could help to detect the condition.